(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of overweight and obesity and to analyze factors associated with overweight and obesity among outpatients with cardiovascular diseases at the Department of Cardiology and Geriatrics, C Hospital, Thai Nguyen Province. Methods: The study was conducted from March to July 2025 using a descriptive, cross-sectional method on 354 outpatients with cardiovascular disease treated at the Department of Cardiology - Geriatrics of Hospital C in Thai Nguyen, Thai Nguyen province. Data were obtained using a structured questionnaire to collect general characteristics and dietary habits, along with anthropometric measurements of body weight and height. Multivariable logistic regression analysis was performed to identify factors associated with overweight and obesity. Results: The prevalence of overweight was 19,8%, including 10,5% in males and 9,3% in females. The prevalence of obesity was 6,7%, with 3,6% in males and 3,1% in females. Sex differences were not statistically significant ( p > 0,05). In contrast, overweight/obesity was significantly associated with the examined variables and a monthly per capita income of ≥ 5 million VND (OR = 2,13; 95% CI: 1,82 - 3,47; p = 0,034), frequent consumption of high-fat foods (OR = 2,66; 95% CI: 1,01 - 2,83; p = 0,018) and frequent consumption of sugar-rich foods and beverages (OR = 2,42; 95% CI: 1,13 - 3,08; p = 0,032). Conclusions: The prevalence of overweight and obesity among outpatients with cardiovascular disease at the Department of Cardiology-Geriatrics, C Hospital, Thai Nguyen Province, remains relatively high. Therefore, close collaboration among physicians, clinical nutrition specialists and nutrition nurses is essential to develop comprehensive care plans, monitoring and nutritional interventions for outpatients, thereby improving treatment effectiveness and quality of life for patients with cardiovascular disease.